Activity-Based Costing Method as an Effort to Increase Profitability - Nur Wahyuni; Ummu Kalsum; Yulan Asmara; Abdul Karim (Jurnal ASET (Akuntansi Riset), 2022)
This study aims to examine the application of activity-based costing as an effort to increase company profitability. This study uses a descriptive qualitative method with an interpretive paradigm with a case study approach, which uses primary data obtained employing interviews, documentation studies, and observations at PT. Anugrah Ocean Wakatamba to break down the elements that make up the cost of goods and service fees using the Activity Based Costing method and then compare them with the service rates used by companies using traditional methods. The results showed that there was undercoating in setting service rates for the type of Ocean Freight 20 feet dry and Ocean Freight 20 feet refer by 35.56% and 9.45% during the period June-December 2021. This leads to the conclusion that the implementation of Activity Based Costing is less effective in increasing company profitability at PT. Anugrah Ocean Wakatamba, but can help companies identify the costs they incur for determining the cost of their services.